Alcyonium bursa Linnaeus, 1758 is not a sponge - van Soest, Rob W.m.; Plotkin, Alexander (Zootaxa, 2021)
In the 10th edition of the Systema Naturae (Linnaeus, 1758), which is the starting point of the Code for Zoological Nomenclature (ICZN Art. 3), Linnaeus named three species of the genus Alcyonium, A. arboreum, A. digitatum, and A. bursa. The genus name Alcyonium was based on the 16th and 17th century pre-Linnaean use for a diversity of marine organisms, including cnidarians, sponges, bryozoans, and algae. In the first valid presentation of the genus name, Linnaeus narrowed this down to comprise two clear cnidarians (A. arboreum, currently Paragorgia arborea, and A. digitatum, still accepted under this name and subsequently assigned as type species), but the pre-Linnaean diversity perhaps explains why the third species, A. bursa, was not recognized as a cnidarian. Linnaeus defined it as ‘Alcyonium acaule pulposum subglobosum. Habitat in O. Europaea.’ (translated as: Alcyonium without stalk, fleshy, semiglobular. From the European Ocean).’ Attempts to fix its identity among contemporary authors at the end of the 18th and beginning of the 19th century followed a checkered course, with opinions varying from algae to tunicates and sponges.